2014
DOI: 10.2152/jmi.61.291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the intake of <i>Undaria pinnatifida </i>(Wakame) and its <i>sporophylls </i>(Mekabu) on postprandial glucose and insulin metabolism

Abstract: Long-term suppression of postprandial glucose concentration is an important dietary strategy for the prevention and treatment of type 2 diabetes. Because previous reports have suggested that seaweed may exert anti-diabetic effects in animals, the effects of Wakame or Mekabu intake with 200 g white rice, 50 g boiled soybeans, 60 g potatoes, and 40 g broccoli on postprandial glucose, insulin and free fatty acid levels were investigated in healthy subjects. Plasma glucose levels at 30 min and glucose area under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…cocoa and grapes, increase cerebral blood flow. Tanemura et al (2014) examined the postprandial blood glucose profiles of 12 healthy adults (eight men, four women, average age 25) after a meal with and without the inclusion of fresh, cooked, whole U. pinnatifida (wakame), or sporophylls of U. pinnatifida (mekabu). An average Japanese cooked breakfast of white rice (200 g), boiled soya beans, broccoli, and potatoes was supplemented with either 70 g fresh wakame or 70 g fresh mekabu.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…cocoa and grapes, increase cerebral blood flow. Tanemura et al (2014) examined the postprandial blood glucose profiles of 12 healthy adults (eight men, four women, average age 25) after a meal with and without the inclusion of fresh, cooked, whole U. pinnatifida (wakame), or sporophylls of U. pinnatifida (mekabu). An average Japanese cooked breakfast of white rice (200 g), boiled soya beans, broccoli, and potatoes was supplemented with either 70 g fresh wakame or 70 g fresh mekabu.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…The small mekabu shoots that grow from the parent wakame seaweed thallus are more viscous when cooked. This is due to their higher content of soluble viscous fibre, which affects carbohydrate metabolism and delays gastric emptying (Tanemura et al 2014). It was concluded that the addition of fresh, brown seaweed to meals could be useful in controlling blood glucose levels for people with type 2 diabetes.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…The consumption of commercial blend of Ascophyllum nodosum and Fucus vesiculosus was associated with improved insulin regulation and sensitivity, measured in human subjects using the Cederholm index upon carbohydrate ingestion, compared with placebo [ 45 ]. Consumption of mekabu (sporophylls of Undaria pinnatifida ) with a white rice-based breakfast by healthy volunteers demonstrated a reduction of post-prandial glucose concentration and this was attributed to the content and viscosity of fucoxanthin in mekabu [ 46 ]. Recently, a study involving more than 4000 participants in Korea revealed that insulin level and insulin resistance were inversely associated with dietary intake of flavonols and flavones, thereby reducing the risk of T2DM [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study investigated the enrichment of a test meal enriched with Wakame and Mekabu, two nutritionally identical preparations obtained from U. pinnatifida characterized by different viscosities. The Mekabu meal significantly reduced the postprandial blood glucose levels (30 min) and glucose AUC, modifying the high glycaemic index of white rice, thus confirming the usefulness of this brown seaweed in controlling T2DM [ 177 ].…”
Section: Clinical Studies Investigating Brown Seaweeds For Ms Treamentioning
confidence: 89%